Predictors of parasite and pathogen infections in urban rodents of central Argentina - Fitte, Bruno; Cavia, Regino; Robles, Maria del Rosario; Dellarupe, Andrea; Unzaga, Juan Manuel; Navone, Graciela Teresa (Journal of Helminthology)
Urban rodents are associated with parasites and pathogens, which present health risks forhumans, but information on factors related to parasite and pathogen infection in rodentsin cities of Latin America is scarce. This study analyzes the hosts, host community structureand environmental characteristics of parasite and pathogen fauna present in the three speciesof urban rodents in an urban area of South America. Rodents were captured seasonally inseven different neighborhoods. Digestive tracts were dissected under stereoscopic microscopyand feces were processed using a sedimentation technique. Protozoa and bacteria weredetected through polymerase chain reaction and indirect immunofluorescence techniques.In Rattus norvegicus, Rattus rattus and Mus musculus, ten helminths, three protozoa andtwo bacteria were found. Six were zoonotic: Toxoplasma gondii; Hymenolepis diminuta;Rodentolepis nana; Strobilocercus fasciolaris; Leptospira borgpetersenii; and Leptospira interrogans. The parasite and pathogen infections were influenced by the host species, the hostcommunity structure, the season, and the presence of streams in the neighborhood. Urbanrodents may be the infection source of many zoonotic diseases and it is important to generatepublic policies for this problem. This study is one example of the situation of many cities ofLatin America, where peripheral neighborhoods are growing dramatically. Fil: Fitte, Bruno. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata. Centro de Estudios Parasitológicos y de Vectores. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Centro de Estudios Parasitológicos y de Vectores; Argentina Fil: Cavia, Regino. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Ciudad Universitaria. Instituto de Ecología, Genética y Evolución de Buenos Aires. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Instituto de Ecología, Genética y Evolución ...